The effectiveness of using text and pictograms on oral rehydration, dry-mixture sachet labels - Jeanne Heyns; Mea van Huyssteen; Angeni Bheekie (AOSIS, 2021)
Background: Medication labels are often the only information available to patients after obtaining medication from a healthcare practitioner. Pictograms are graphic symbols that have shown to increase understanding of medicine use instructions. Aim: To compare the accuracy of the interpretation of medicine use instructions from two different oral rehydration (OR) dry-mixture sachet labels - the control 'routine textonly' label and an experimental label with 'text-and-pictograms'. Setting: Participants were recruited from waiting rooms in public primary health care (PHC) facilities in Cape Town. Method: Each participant was required to answer six questions about OR preparation. Response accuracy was determined by comparing the participant's answer to the actual information written on the relevant label. Afterwards, participants could offer their opinion about the label and ways to improve their understanding. Results: Of the 132 participants who were recruited, 67 were allocated to the experimental group and 65 to the control group. Only the significant difference between the experimental and control groups for the six questions regarding the label, was recorded for the answer that could be read from a single pictogram (p = 0.00) on the experimental group's label. When asked about this question, more control participants (15/65) found the dosing instruction difficult to understand when compared to the experimental group (1/67). A third of the control participants (22/65) indicated that they could not see or locate instructions on the label. Conclusion: Text and pictograms on written medicine labels may be an effective tool to aid understanding of medicine use instructions amongst patients attending PHC facilities.